PENERAPAN PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN PEMAHAMAN KONSEP GERHANA MATAHARI DAN GERHANA BULAN SISWA KELAS VI SD NEGERI 160 PALEMBANG - Susanti, Febby; Arni, Yusni; Rahmadini, Riska; Anggraini, Auliya Wanda (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to improve sixth-grade students’ understanding of solar and lunar eclipses at SD Negeri 160 Palembang through the Project-Based Learning (PjBL) approach. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. The participants consisted of 31 students. Data were collected through observation and assessment and analyzed using both qualitative and quantitative methods. The results showed that the implementation of PjBL improved students’ conceptual understanding of eclipses. The average achievement score increased from 70.90 at the initial stage to 75.65 at the end of Cycle I, and further to 80.90 at the end of Cycle II. The level of learning mastery also improved significantly from 45% to 82%. In addition, the PjBL approach effectively motivated students to actively engage in learning, collaborate with peers, and demonstrate enthusiasm throughout the learning process. In conclusion, Project-Based Learning is an effective approach for enhancing students’ understanding of scientific concepts, particularly in learning about solar and lunar eclipses at the elementary school level.